LIVER EXPLANATION TECHNOLOGY OPTIMIZATION - Разумов, Александр Сергеевич; Вавин, Григорий Валерьевич; Будаев, Алексей Владимирович; Радионов, Игорь Александрович; Сидорова, Ольга Дмитриевна; Ставицкий, Е. Е.; Раева, Дарья Александровна; Будаев, Ф. А.; Мозес, Вадим Гельевич (Medicine in Kuzbass, 2020)
Objective – to reduce mechanical and ischemic damage to the liver during explantation.Materials and methods. An experiment was conducted on liver explantation on 14 sexually mature outbred rabbits of both sexes with zoetil anesthesia. In comparison with the traditional method of liver explantation, the proposed technique had the following differences: the mobilization of the stomach and intestinal loops was performed with their displacement to the left and down, which provided optimal access to the mesenteric veins and the posterior (inferior) vena cava; portal vein catheterization was performed through the anterior mesenteric vein, which reduced the risk of catheter expulsion; liver extraction was performed as part of the liver-diaphragm complex using clamps on the diaphragm, which reduced the risk of organ trauma; The washing of the vascular bed of the liver from the blood began even before the complete completion of the mobilization of the organ and ended almost immediately after its extraction, which reduced the duration of primary ischemia.During explantation, the vascular bed of the liver was washed from the blood with a 0.9 % sodium chloride solution with the addition of heparin (500 ME/kg) under a pressure of 20-35 mmHg antegrade along an open circuit through a catheter in the portal vein with an outflow through the catheter in the inferior vena cava until a perfusate appears in which blood was not visually detected. The animals were divided into 2 series: 1st series (n = 6), which were washed using normothermic perfusion (solution at 37 ± 1°C); 2nd series (n = 8) with which washing was carried out using hypothermic perfusion (solution with a temperature of 3 ± 1°C). After 14 hours of liver preservation, its histological examination was performed.Results. Experimental testing of the developed liver explantation algorithm showed a decrease in the laboriousness and invasiveness of the operation, which was expressed in a reduction in the time of its implementation and in a decrease in morphological changes in the transplants during subsequent prolonged static hypothermic preservation.
Keywords: liver transplantation; explantation; viability of liver transplantates; perfusion; normothermia; hypothermia